MENINGKATKAN KEWASPADAAN MASYARAKAT TERHADAP PENYEBARAN COVID-19 PADA MASA NEW NORMAL DI KABUPATEN SIDOARJO - Dewi Sukriyah; Siti Nuriyatin (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2021)
This activity aims to disseminate information about the importance of implementing 3M during the COVID-19 pandemic, distribute masks and hand sanitizer. Covid-19 pandemic is not over yet. But community activities began to be carried out again in the new normal. Many people have disobeyed health protocols. This is one of the reasons for the need to re-socialize the importance of health protocols. This activity was held in several areas of Sidoarjo. The method in this activity is counseling. The result of this activity is an increase in public awareness of COVID-19. Keywords: Covid-19, New Normal, health protocol